2009
DOI: 10.1071/wf07122
|View full text |Cite
|
Sign up to set email alerts
|

An inverse method to estimate stem surface heat flux in wildland fires

Abstract: Abstract. Models of wildland fire-induced stem heating and tissue necrosis require accurate estimates of inward heat flux at the bark surface. Thermocouple probes or heat flux sensors placed at a stem surface do not mimic the thermal response of tree bark to flames. We show that data from thin thermocouple probes inserted just below the bark can be used, by means of a one-dimensional inverse heat conduction method, to estimate net heat flux (inward minus outward heat flow) and temperature at the bark surface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This configuration (Figure 2(b)) was used because it simulates a realistic position of the bark in relation to the incident heat flux. 15 A vertically positioned EPI was used to generate a heat flux of 25 kW m 22 . This device was calibrated using a Fluxmeter in order to correlate 10 different emission heat values (measured in watts according to ISO 5657) with the corresponding emitted heat flux (kW m 22 ).…”
Section: Devices and Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…This configuration (Figure 2(b)) was used because it simulates a realistic position of the bark in relation to the incident heat flux. 15 A vertically positioned EPI was used to generate a heat flux of 25 kW m 22 . This device was calibrated using a Fluxmeter in order to correlate 10 different emission heat values (measured in watts according to ISO 5657) with the corresponding emitted heat flux (kW m 22 ).…”
Section: Devices and Protocolsmentioning
confidence: 99%
“…[10][11][12] Use of these devices also enables basic characterization of the combustion process. 13,14 Bova and Dickinson 15 proposed an inverse method for estimating the stem surface heat flux that occurs in wildland fires from data obtained in laboratory experiments; however, the protocol and device did not enable characterization of flammability or response to fire. Recently, Chen et al 16 analysed the effect of incident heat flux angle (horizontal vs. vertical configuration) in cone calorimeter experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In their radiative heating experiment using a tree stem, Bova and Dickinson found that surface‐mounted thermocouple probes overestimated the surface temperature because of lower emissivity of the thermocouple than that of the surface. The situation was reversed at the fabric's back surface, which faced the water‐cooled HFT, and thus, the thermocouple would underestimate the surface temperature.…”
Section: Resultsmentioning
confidence: 99%